2016
DOI: 10.1002/ccd.26650
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding following transcatheter aortic valve replacement: A retrospective analysis

Abstract: This large cohort study demonstrates that TAVR is associated with a moderate risk of severe UGIB. The results of this study suggest that patients on triple antithrombotic therapy are at highest risk for severe UGIB. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Our analysis indicates that treatment with TT or SAC is associated with adverse clinical outcomes compared to treatment with AP alone after TAVR, which is consistent with findings from other studies of patients undergoing TAVR [ 17 , 18 ] and surgical aortic valve replacement [ 19 ]. We did not observe a benefit on ischemic endpoints with regimens using 2 or 3 antithrombotics compared to AP alone, as rates of MI and stroke were similar among the three treatment groups, but the study was not powered to do so.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis indicates that treatment with TT or SAC is associated with adverse clinical outcomes compared to treatment with AP alone after TAVR, which is consistent with findings from other studies of patients undergoing TAVR [ 17 , 18 ] and surgical aortic valve replacement [ 19 ]. We did not observe a benefit on ischemic endpoints with regimens using 2 or 3 antithrombotics compared to AP alone, as rates of MI and stroke were similar among the three treatment groups, but the study was not powered to do so.…”
Section: Discussionsupporting
confidence: 91%
“…The overall rate of both upper and lower GIB bleeding was 1.4% in our cohort. Similarly, a study on 841 patients undergoing TAVR reported an incidence of 2% for upper GIB in the immediate post TAVR period [10]. For comparison, the rate of GIB within 30 days and after 30 days of TAVR have were reported to be 2.41% and 5.4%, respectively (7,8) The most common culprit lesion found during endoscopy in our cohort was angiodysplasia occurring in 0.6% of patients.…”
Section: Discussionsupporting
confidence: 58%
“…Some studies have reported that patients on postprocedural triple antithrombotic therapy were at the highest risk for severe upper GIB. More specifically, these patients were found to be at a >10-fold higher risk of upper GIB when compared to patients not on triple antithrombotic therapy [10].…”
Section: Discussionmentioning
confidence: 92%
“…Stanger et al in a single center retrospective evaluation showed that TAVR is associated with a moderate risk of severe UGIB. Patients on triple antithrombotic therapy are at highest risk for severe UGIB [32]…”
Section: Discussionmentioning
confidence: 99%